1989
DOI: 10.1001/archotol.1989.01860340098026
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium: The New Gold Standard for Diagnosing Cerebellopontine Angle Tumors

Abstract: \s=b\All physicians involved with the diagnosis and management of patients with tumors in the temporal bone and cerebellopontine angle are faced with the challenge removing these tumors while preserving hearing. Part of the challenge is to make the diagnosis while the tumor is still small enough to attempt a hearing-conservation surgical approach. Air-contrast (air cisternography) computed tomography is the "gold standard" by which all techniques of diagnosis are compared. Most physicians, however, are relucta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…VS, also known as acoustic neuroma (AN), is the most common tumor of this area [1]. Gadolinium-enhanced magnetic resonance imaging (MRI) is currently considered the gold standard for imaging VS. Its efficacy has been proven and its sensitivity could detect tumor as small as 4 mm [1,2]. However, investigation with MRI is expensive, not always easily available and not acceptable for all patients, especially claustrophobic patients or patients with pacemaker and clipped aneurysms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VS, also known as acoustic neuroma (AN), is the most common tumor of this area [1]. Gadolinium-enhanced magnetic resonance imaging (MRI) is currently considered the gold standard for imaging VS. Its efficacy has been proven and its sensitivity could detect tumor as small as 4 mm [1,2]. However, investigation with MRI is expensive, not always easily available and not acceptable for all patients, especially claustrophobic patients or patients with pacemaker and clipped aneurysms.…”
Section: Introductionmentioning
confidence: 99%
“…The main goals of this study were: (1) to compare all the definitions of asymmetric SNHL reported in literature; (2) to measure the agreement between these definitions in detecting VS; and (3) to determine the strongest association between an asymmetric SNHL definition and positive VS on MRI.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Radiological assessment is therefore crucial, with gadolinium-enhanced magnetic resonance imaging (MRI) of the internal auditory meatus recognised as the 'gold standard' for investigating asymmetrical SNHL. 5 With such wide-ranging symptomatology for vestibular schwannoma, increasing numbers of MRI scans of the internal auditory meatus are being performed. 6 This has led to a rise both in the number of scans reported as normal and those with incidental clinical findings.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) with Gadolinium enhancement is regarded as the gold standard in diagnosing CPA lesions. Still, MRI is expensive, time-consuming and considered burdensome for many patients (2,3). Moreover, when we contemplate the necessity of further diagnostic work-up, one must consider that only a small percentage of patients with asymmetric hearing loss will indeed be diagnosed with a CPA lesion.…”
mentioning
confidence: 99%